Aquatic habitat shift assessment in a groundwater-fed semi-arid stream: an investigation into the response of Karoo hydroecology to system variability - Ellis, Natalie (Rhodes University, Faculty of Science, Department of Geography, 2018)
From introduction: The subject of biological response to changes in aquatic habitat is one which has been well explored in many regions of the world. Examples include work in south east Spain by Mellado Diaz et al. (2008) and Oliva-Paterna et al. (2003), in western United States of America by Hauer and Lorang (2004), and in West Germany by Meyer et al. (2003). Similarly, a number of studies have been conducted in semi-arid regions, exploring elements such as erosion, climate, lithology and landscape formations (e.g. Boardman et al., 2013; Le Maitre et al., 2007; Meyer et al., 2003). However, apart from the study by Uys (1997), and Uys and O'Keeffe (1997), there is a noticeable lack of literature on aquatic habitat shifts in semi-arid stream systems, despite these systems being recognised for their high natural variability. This study provides a base-level approach to conducting habitat shift assessments in a semi-arid stream system and monitoring the hydroecological responses to system variability.
Keywords: Aquatic habitats -- South Africa -- Karoo; Arid regions -- South Africa -- Karoo; Biotic communities -- South Africa -- Karoo; Stream ecology -- South Africa -- Karoo